A conversion analysis of so-called coercion from relational to qualitative adjectives in English. (July 2018) - Nagano, Akiko
Abstract : It is widely observed that relational adjectives (RAdjs) in English can be coerced into qualitative adjectives (QAdjs) rather freely (Farsi 1968 ;Beard 1991 ;Bauer et al. 2013 ;Nikolaeva & Spencer 2013 ;Lieber 2015 ). However, the process of coercion and its output properties have not been studied extensively. This paper presents a conversion analysis of the process and discusses how it is effected in the grammar and how converted QAdjs differ from non-converted suffixal ones, such as similatives. The analysis considers the working of the truthfulness operator within a class name NP. Clearly demarcating different adjective classes, the findings of this paper contribute to research on both conversion and RAdj.